Distribution Pattern of Anchorage Stress and Water Sensitivity Analysis of Red Clay - Lifeng Li; Weili Gong; Huilin Deng; Xiaohu Zhang; Gan Li (Shock and Vibration)
Red clay is a special soil layer with complex engineering properties distributed in tropical and subtropical regions. An anchor cable support is a common form of red clay slope support. The effectiveness of the anchor cable support is mainly determined by the anchoring force provided by the red clay stratum. Increase of the water content will lead to the rapid deterioration of the mechanical properties of red clay, which will lead to the reduction of the anchoring force of the slope anchor cable and lead to the failure of the support. Based on the classical Phillips and uniform anchorage shear stress distribution theory, this paper puts forward a uniform-exponential distribution pattern of anchorage shear stress according to the specific characteristics of red clay by using the characteristics of the peak shear strength and residual shear strength of the rock and soil mass. With increasing anchorage force, the dynamic evolution (single exponential distribution ⟶ double single exponential distribution ⟶ uniform index exponential complex distribution ⟶ uniform distribution) of the anchorage shear stress is analysed. Based on the peak and residual test of the cohesive force and internal friction angle, the relationship between the anchoring force and buried depth and water content is established by analysing the factors influencing the anchoring force. It can be found from the field test that, according to the relationship established, the limit anchorage force of the anchor cable in the red clay stratum can be calculated and the water sensitivity of the anchor cable’s limit anchorage force can be quantitatively analysed.